Personality and study environment as determinates of learning motivation in higher education - Müller, Florian H. (2010)
This study investigates the question how well the personality and the perceived learning environment predict self-determined learning motivation in higher education. Previous research has predominantly focused on the interrelation between learning environment and self-determined learning motivation. The theoretical basis of the study is the ‘Big Five’ personality model (Goldberg, 1999 ; McCrae, et al. 2000) as well as the self-determination theory (Deci & Ryan, 2002). We have examined the data of 1534 Croatian students with cluster and regression analyses. The dependent variable is self-determined learning motivation ; independent variables are personality traits (Big Five), and the perception of the teaching-learning environment (including the support of basic needs and other relevant variables for instruction). The results of the analyses show that the self-determination theory is also valid in a south-eastern cultural context and that personality variables and the environment are significant predictors for intrinsic learning motivation and autonomous forms of extrinsic motivation. A further significant result is that students’ perceived self-determination decreased after the implementation of the so called 'Bologna process' in Croatia.